Perception of Pathology Online Classes for MBBS (Pre-Clinical Students): A Covid Generated Evolution - Pande, Kricha; Joshi, Sammi (Nepal Medical College Journal, 2022)
The unexpected COVID-19 crisis has disrupted medical education and patient care in unprecedented ways. As the pandemic occurred unexpectedly, University and its affiliated colleges, their faculty members had to hurriedly switch to online courses without reflecting on how to transform the curriculum to align well with the online learning platform. As Nepal Medical College, Teaching Hospital (NMCTH) had also embraced e-learning as teaching learning tools in undergraduate students, this study tried to focus on the participation and satisfaction rate of students regarding the same. This is a cross-sectional descriptive study conducted at NMCTH. MBBS second year students (Pre-clinical years) were given a validated, anonymous, self-administered questionnaire to fill in. The following categories were looked for: 1) participation in the online classes and 2) level of satisfaction of online class in Pathology subject. The questionnaire consist a total of 14 questions and answers were given in the form of yes/ no or option wise. Out of total of 98 students, 95 students responded. Most of MBBS second year students (69%) felt that online classes were not as effective as physical classes and were also not satisfied with this method of teaching. Most of the students (88%) felt that they paid more attention in physical classes than online classes. However, they didn’t find any differences between the physical or online examinations. Mobile phones were the most used device and Microsoft teams was the preferred platform. Despite the interference of learning due to network problem, the audio and video quality was satisfactory. The participation in online classes was good. The advantages were that there was no disturbance from fellow class mates during online class as stated by 68% of participants. There was room for open discussions and interaction with teacher (60%) just as in case of physical lectures. The major disadvantage was that most of the students were not satisfied with this method of learning and they find it ineffective compared to physical classes. Thus from this study, we can conclude that students prefer physical classes and online classes cannot replace the physical classes. However, with the implementation of online classes, we can ensure that it has overcome the vent created by Covid-19 pandemic.